إيجاد الثقافة الجديدة في القرآن الكريم بالانتقاء التقابلي للمفردات (نموذج من الاعجاز القراني): Creating a New Culture by Choosing Opposite Lexical Terms in the Holy Qur’an - Dialameh, Nikoo; Mohseninejad, Soheila (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
The Holy Qur'an, as it introduces itself is a life-giving (that which gives you life), healer (healing for the diseases in your hearts), cultural creator (taught you, which ye knew not before), reformer (improve their condition) and savior (ye were on the brink of the pit of Fire, and He saved you from it). In this regard, in addition to the deep meaning and content along with the unique literary devices and techniques that have impressed the listeners, the Quran has a unique style in the selection and words usage. One of these methods used in creating a culture is how the Quran employs opposite lexical terms. The kind of contradiction that the Qur'an has invented by selecting words is not customary. By utilizing descriptive-analytical method, the purpose of this study is to demonstrate some Qur'anic contradictions and the logic behind it in order to create a new culture among the audience. The findings show that in many cases, the Holy Quran has not followed the common structure of using opposite words, but it has used a new method to institutionalize a new culture among its audience. This being the case of using the word rahmah against shiddah instead of al-lin depicting the mercy as the cause of gentleness. Furthermore, the use of ithm against nafa’ instead of dharar where it shows that every sin is harmful to human. The findings also prove that this Qur'anic method leads the audience to a better understanding of the meanings and concepts of the Holy Qur'an. Apart from its miraculous model of heavenly scripture, this method or style has made possible to convey a larger volume of knowledge in abbreviated terms and the extent to which the new culture can be built not to mention the development and presentation of broader concepts in audience's mind.